Perahu Pangalengan - Abrianto, Octaviadi (PANALUNGTIK, 2019)
People of Warnasari village found an iron boat on the bottom of Situ Cileunca Lake, the boat is made from iron sheets with flat keel. The iron sheets was bound together using iron rivets and the boat have hooks that look like use to attact to other boats. Flat keel boat usually use on calm water such as river or lakes, boat using rivet usually build before 1930?s as after that year boats were build using welding technic. It?s assumed that boat from Situ Cileunca was used for ferrying goods or peoples, the exact function can?t determine precisely due to lack of data.